MENINGKATKAN KEMAMPUAN KOGNITIF ANAK DALAM MENGENAL DAN MENULIS ANGKA MELALUI BERBAGAI MEDIA DI TK AISYAH MUARA MUSU - Roslan, Roslan (Universitas Pasir Pengaraian, 2017)
ABSTRACTThis research was a class action research (CAR). It was aimed to improve studentcognitive competence in identify and write number through some medias at AisyahMuara Musu. The population of this research is 17 students. This research consistedof two cycles with the first cycle and second cycle consists of five meetings. Thedata collection technique in this study was done by using observation techniques.This technique used the observation sheet. This was analyzed with comparecognitive value of two cycles. This was aimed to know cognitive competenceimprove in identify and write number through some medias. The result of theresearch showed that there was an improvement of studentsâ€™ cognitive competence inidentify and write number through medias at TK Aisyah Muara Musu. At cycle 1,there were 35% students got very good, 18% student got good, and 47% needssupervise. While at cycle 2, there were 82% students got very good, 12% student gotgood, and 6% needs supervise.Â